If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + -1) = 157 Reorder the terms: x + (-1 + x) = 157 Remove parenthesis around (-1 + x) x + -1 + x = 157 Reorder the terms: -1 + x + x = 157 Combine like terms: x + x = 2x -1 + 2x = 157 Solving -1 + 2x = 157 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2x = 157 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = 157 + 1 2x = 157 + 1 Combine like terms: 157 + 1 = 158 2x = 158 Divide each side by '2'. x = 79 Simplifying x = 79
| 25v^2+45v+14=0 | | 5x-7=-2x+14 | | 86-4h=76+4h | | v^2=3x | | 9(x+4)+8=9x+8 | | 5+LN(3x+7)=12 | | 60x^2-60=0 | | x=-0.666666666667 | | 6x^3-7x^2-3x=0 | | 25v^2+45v+21=0 | | 2x-8=-4x+24 | | 2(3x+7)=-30 | | 2r-10r-14=-2 | | n(n-1)/2=105 | | (a-1)+(b+3)i=5+8i | | X^2=10x-5 | | -5+6x=67 | | n(n01)/2=210 | | 9m-22=4m+4 | | x+7x=408 | | 48k^2-222k+120=0 | | 9/10-4.5 | | y=6+4(-27) | | 16x-56=-4+4 | | 27x+72x= | | 140=10x-.1x^2 | | (x-3)x^2-4=0 | | Eln(2x)3=32 | | (3x+5)4=5(4x-4) | | 3Ln(x)=10 | | 4a+5=23 | | -5x-6+4x=21 |